Managing the genome: microRNAs in Drosophila. - Gesellchen, V.; Boutros, M. (Differentiation, 2004)
MicroRNAs (miRNAs) represent a growing class of short non-coding RNAs that regulate gene expression by post-transcriptional mechanisms. By binding to target mRNAs via stretches of sequence complementarity, microRNAs inhibit the production of target proteins or induce degradation of mRNAs. Several hundred miRNAs have recently been predicted and cloned from eukaryotic organisms as diverse as plants, invertebrates, and vertebrates. Some miRNAs were shown to be widely conserved across phyla. However, except in a few described cases, rather little is known about their endogenous target genes and the physiological pathways they impinge on. Invertebrate model organisms such as C. elegans and Drosophila have been instrumental to develop methods and to dissect biological roles of miRNAs. In this review, we will focus on recent progress in characterizing miRNAs and steps toward identification of target genes in Drosophila. Many of these recent experiments provide evidence that a systematic target discovery is feasible and that the biology of miRNAs can be functionally explored using forward and reverse genetic tools.